Mobile Application for the Automation of Reservation and Incident Processes for Condominiums - Asto-Aguilar, Dolly (2022)
Technological advances make more and more companies transform their manual processes into automated processes, increasing the speed and efficiency of their operations. That is the reason for this research, to test the benefits of automating the administrative processes of the Nuevavista condominium under study located in Peru, focusing on the management of reservations and incidents through the development of a mobile application following the mobile-d methodology. The article resorts to the use of a pre-experimental design with a sample of 279 for each process. The results indicate a 71% reduction in the time to register common area reservations and 69% in the time to register incidents, as well as a reduction in the number of people involved in both processes, which used to be two to four people, to one person, and finally, satisfaction levels were raised from 2 to 5 for the management of reservations and incidents.